Interdisciplinaridade no ensino jurídico: reflexões a partir da percepção de docentes e discentes do curso de direito da Universidade Federal do Amazonas (UFAM) - (:unkn) unknown (Universidade Federal do Amazonas, 2018)
This thesis aims to reflect on the interdisciplinarity in legal education from the perception of teachers and students of the law course of the Federal University of Amazonas (UFAM). In order to reach this general proposal, it adopted as specific objectives: a) To present the trajectory of the interdisciplinary studies in Brazil, highlighting the points of convergence and the distinctions between different theorists, contemplated in the inaugural chapter of this work; b) To characterize the epistemological paradigms and the panorama; (c) Analyze the pedagogical nuances of interdisciplinarity delimited from the perception of teachers and students of the law course of the Federal University of Amazonas (UFAM), corresponding to the third chapter of the thesis; and finally c) Propose some pedagogical possibilities interdisciplinary to the course of Law from the idea of complexity. This research is quantitative-qualitative, since we opted for the punctual analysis of the Political Educational Project of the Law course of UFAM and the perception of teachers and students of this institution.
Interdisciplinarity in legal teaching: reflections from the teachers and disciples perception of the course of law of the Universidade Federal do Amazonas (UFAM)
Keywords: Ensino jurídico; Paradigmas; Complexidade; Interdisciplinaridade; CIÊNCIAS HUMANAS